Transcriptomic analysis of vitamin D responses in uterine and peripheral NK cells. Issue 2 (August 2019) - Tamblyn, J A; Jeffery, L E; Susarla, R; Lissauer, D M; Coort, S L; Garcia, A Muñoz; Knoblich, K; Fletcher, A L; Bulmer, J N; Kilby, M D; Hewison, M
Abstract : Vitamin D deficiency is prevalent in pregnant women and is associated with adverse pregnancy outcomes, in particular disorders of malplacentation. The active form of vitamin D, 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3), is a potent regulator of innate and adaptive immunity, but its immune effects during pregnancy remain poorly understood. During early gestation, the predominant immune cells in maternal decidua are uterine natural killer cells (uNK), but the responsivity of these cells to 1, 25(OH)2 D3 is unknown despite high levels of 1, 25(OH)2 D3 in decidua. Transcriptomic responses to 1, 25(OH)2 D3 were characterised in paired donor uNK and peripheral natural killer cells (pNK) following cytokine (CK) stimulation. RNA-seq analyses indicated 911 genes were differentially expressed in CK-stimulated uNK versus CK-stimulated pNK in the absence of 1, 25(OH)2 D3, with predominant differentially expressed pathways being associated with glycolysis and transforming growth factor β (TGFβ). RNA-seq also showed that the vitamin D receptor ( VDR ) and its heterodimer partner retinoid X receptor were differentially expressed in CK-stimulated uNK vs CK-stimulated pNK. Further analyses confirmed increased expression of VDR mRNA and protein, as well as VDR-RXR target in CK-stimulated uNK. RNA-seq analysis showed that in CK-stimulated pNK, 1, 25(OH)2 D3 induced 38 and suppressed 33 transcripts, whilst in CK-stimulated uNK 1, 25(OH)2 D3 induced 46 and suppressed 19 genes. However, multiple comparison analysis of transcriptomic data indicated that 1, 25(OH)2D3 had no significant overall effect on gene expression in either CK-stimulated pNK or uNK. These data indicate that CK-stimulated uNK are transcriptionally distinct from pNK and, despite expressing abundant VDR, neither pNK nor uNK are sensitive targets for vitamin D.